On the Effect of Learning Style on Scholastic Achievement - Rahmat Ulllah Bhatti; William M Bart (Current Issues in Education, 2013)
The present study was designed to explore the influence of learning styles on scholastic achievement levels.  The participants in this study were undergraduate students studying social sciences at a Division 1 research university, The frequencies of the participants in the four learning style categories are the following: Convergent (n = 28), Divergent (n = 49), Assimilator (n = 76), and Accommodator (n = 40). The instruments used in the study were the Kolb learning style inventory and a demographic form. The major findings of the study are that the dominant learning style was Assimilator and that learning style and gender influenced academic achievement.